Polyvinyl alcohol cryogel based vessel mimicking material for modelling the progression of atherosclerosis. (January 2020) - Malone, Andrew J.; Cournane, Sean; Naydenova, Izabela G.; Fagan, Andrew J.; Browne, Jacinta E.
Highlights: The mechanical properties of polyvinyl-alcohol cryogel depend on its sample volume. The dumbbell test objects of ISO37 are mechanically analogous to vessel mimics. PVA-c can be used to produce vessel mimics with high geometric reproducibility. Abstract: Purpose: The stiffness of Polyvinyl-alcohol cryogel can be adjusted through application of consecutive freeze-thaw cycles. This material has potential applications in the production of tissue mimicking phantoms in diagnostic ultrasound. The aim of this study was to use PVA-c to produce a range of geometrically and acoustically identical vessel phantoms modelling stages of atherosclerosis which could be verified through mechanical testing, thus allowing for more precision in quantitative in-vitro flow analysis of atherosclerosis. Methods: A series of anatomically realistic walled renal artery flow phantoms were constructed using PVA-c. In order to ensure precise modelling of atherosclerosis, a modified procedure of ISO27:2017 was used to compare the mechanical properties of PVA-c. Results were compared for the standard "dumbbell" test object and a modified vessel test object. The geometric accuracy and reproducibility of the vessel models were tested before and after implantation in flow phantoms. Results: No significant difference was found between the mechanical properties of the dumbbell test samples and the vessels for any number of freeze thaw cycles, with a correlation coefficient of R 2 = 0.9767 across the dataset, indicating that a direct comparison between the mechanical properties of the dumbbell test samples and the phantom vessels was established. The geometric reproducibility showed that before and after implantation there was no significant difference between individual vessel geometries (p = 0.337 & p = 0.176 respectively). Conclusions: Polyvinyl-alcohol cryogel is a useful material for the production of arterial flow phantoms. Care should be taken when using this material to ensure its mechanical properties have been correctly characterised. The guidelines of ISO37:2017 potentially provide the best procedure to ensure this.